Design and development of highly conserved, HLA-promiscuous T cell multiepitope vaccines against human visceral leishmaniasis - Barreto, Aline Silva; de Franca, Mariana Nobre Farias; dos Reis, Tatiana Leão dos Santos; Silva, Joao Antonio Barbosa Martins; Dos Santos, Priscila Lima; de Oliveira, Fabrícia Alvisi; da Silva, Angela Maria; Magalhaes, Lucas Sousa; Secco, Danielle Angst; Andrade, Maria Aiza Fontes; Porto, Luís Cristóvão; Rosa, Daniela Santoro; et al. (Frontiers in Immunology, 2025)
IntroductionNo vaccine is currently licensed against human visceral leishmaniasis (VL), a fatal CD4+ T cell immunosupressive disease against which chemotherapy is reduced to a few toxic drugs. The NH36 nucleoside hydrolase is a DNA metabolism vital enzyme present in all Leishmania species. A vaccine based on such a conserved antigen could protect against both VL and cutaneous leishmaniasis, whose epidemics geographically overlap. Increased frequencies of NH36-specific IL-2+TNF-α+IFN-γ+-producing CD4+ T cells were associated with VL immune protection.Methodsthe sequences of HLA-Class I and Class II T cell epitopes were predicted in the NH36 peptide sequence using the Tepitope, Propred, IEDB and NetMHCpan EL 4.1 immune informatic tools. The epitopes were synthetized and used to study their reactivity with sera samples, and to stimulate the in vitro response of PBMC of human patients cured from VL, asymptomatic individuals and healthy blood donors of a non-endemic area. Cytokine production was studied intracellularly by flow cytometry (ICS) and cytokine secretion was measured in PBMC supernatants. The HLA typing of DNA patients and the analysis of epitope conservancy in the Leishmania genus were obtained. Two recombinant multiepitope proteins were designed, cloned in E. coli, expressed, purified and used for in vitro stimulation of PBMC of VL cured and asymptomatic patients.ResultsWe identified in silico fifteen NH36 conserved epitopes that correspond to promiscuous binders of HLA-DR, -DQ, -DP class II molecules, as well as HLA-A, B and C class I molecules. Collectively, these epitopes provide high worldwide population coverage of both class I and II alleles, and bound to alleles associated with VL susceptibility and resistance. VL asymptomatic individuals showed maximal frequencies of CD4+ and CD8+ multifunctional IL-2+TNF-α+IFN-γ+-producing T lymphocytes in response to these epitopes, with secretion of TNF-α, IL-1β and IL-6. Two recombinant multiepitope vaccines were designed using these epitopes linked by AAA or GPGPG spacers. Both proteins promoted CD4+ and CD8+ T cell responses in PBMC of VL cured and asymptomatic individuals.DiscussionBoth MultiAAA and MultiGPGPG proteins could be potentially used for universal human vaccination against leishmaniasis.